Study of Paclobutrazol Dosage and Seed Size on Growth and Yield of Porang (Amorphophallus onchophyllus P.) - Sefti Nurul Hidayah; Ramdan Hidayat; Nova Triani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
The konjac plant (Amorphophallus oncophyllus Prain.) contains high glucomannan with many benefits.  This experiment aimed to study effect of paclobutrazol dose and seedling size on the growth and yield of konjac plants.  The research was arranged factorially based on a Completely Randomized Design with two factor.  The first factor (paclobutrazol dose) consisted of P0: 0.0 g/plant, P1: 0.05 g/plant, P2: 0.10 g/plant, P3: 0.15 g/plant, P4: 0.20 g/plant.  The second factor (seed size) consisted of U1: 20-50 g/seed, U2: 100-150 g/seed, U3: 200-250 g/seed. Observation parameters included plant height, canopy diameter, stem diameter, stem sturdiness, number of buds, weight and diameter of tubers.  Results showed that paclobutrazol dose of 0.20 g/plant had a significant effect on stem sturdiness, weight and diameter of the tubers. The maximum of tuber weight obtained by paclobutrazol application of 0.2 g/plant was estimated to be 1,533 g with tuber diameter of 167 mm.  Small size seed (20-50 g) produced the largest number of buds and did not differ markedly from those of medium size seed (100-150 g).  Large size seed (200-250 g) produced the best konjac plants in term of canopy diameter, stem sturdiness, weight and diameter of tubers. Keywords : Dosage, Konjac, Paclobutrazol, Seed Size, Tuber Size